Neuroendocrine tumors: An epidemiological study of 250 cases at a tertiary hospital - Silveira,Felipe (2017)
Summary Objective: To compare the frequency of neuroendocrine tumors in our service with that reported in the literature considering age, gender, location, degree of differentiation and increase in incidence by means of a retrospective study. Method: Search of variables from a database of neuroendocrine tumor cases diagnosed at the Department of Pathological Sciences, Hospital da Santa Casa de São Paulo over the past 10 years, relating them to epidemiological data such as gender, age, distribution across organs, most-used immunohistochemical markers and presence or absence of either lymph node or distant metastases. Results: In all, 250 cases were reviewed, 133 involving females, predominantly in the 61-70 age range. The lung was the most frequent site, followed by the stomach. CD56, synaptophysin and chromogranin were the immunohistochemical markers used most often and to a lesser extent Ki67, a marker of cell proliferation that indicates a higher or lower degree of histological malignancy. Metastases, either in lymph nodes and/or distant sites, were found in 44 cases (17.6%). Conclusion: The results were largely consistent with those in the literature, including age group, gender and location. Most metastases originated from high-grade tumors, with high Ki67 levels and greater impairment of the liver. However, only 36.4% of the cases had Ki67 index. Reevaluation of the Ki67 proliferative index using image analysis in doubtful cases will allow for a correlation between progression and prognosis.